2003
DOI: 10.1254/jphs.91.71
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Topical CX-659S, a Novel Diaminouracil Derivative, With Topical Corticosteroid on the Three Types of Allergic Responses in Mice or Guinea Pigs

Abstract: Abstract. CX-659S ((S)-6-amino-5-(6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxamido)-3-methyl-1-phenyl-2,4(1H,3H)-pyrimidinedione), a newly discovered anti-inflammatory compound, exerts inhibitory effects against picryl chloride-, oxazolone-, and dinitrochlorobenzeneinduced acute contact hypersensitivity responses (CHRs) characterized by Th1-type reactions. Furthermore, this compound suppressed chronic CHRs characterized by Th2-type reactions, which is well known to mimic many, if not all, events occurring wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…DNCB is an agent that was previously used in many studies to form induced allergic dermatitis in mice [23,24]. In our study we successfully formed atopic dermatitis through the use of local DNCB in all the trial subjects.…”
Section: Discussionmentioning
confidence: 86%
“…DNCB is an agent that was previously used in many studies to form induced allergic dermatitis in mice [23,24]. In our study we successfully formed atopic dermatitis through the use of local DNCB in all the trial subjects.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, compounds that exhibited good bioavailability in rats (>20%) were examined for their anti-inflammatory potential in mice OVA-induced biphasic cutaneous reaction model. 19 Finally, promising compounds were evaluated for their H 1 receptor occupancy in the mouse brain.…”
Section: Resultsmentioning
confidence: 99%
“…The gels were tested in an animal model of AD where AD‐like skin lesions were induced with a strong sensitizer (DNBC) . It has been reported that following DNBC challenge, the mice skin expression of both TH 1 and TH 2 immune responses as well as the production of IgE and TH 2 cytokines is similar to that observed in human patients of AD . On the macroscopic level, the skin of mice treated with DNBC exhibits an AD‐like lesion; that is, it appears dry, red and rough: topical signs of a compromised barrier function .…”
Section: Discussionmentioning
confidence: 99%
“…[34,44,45] It has been reported that following DNBC challenge, the mice skin expression of both TH 1 and TH 2 immune responses as well as the production of IgE and TH 2 cytokines is similar to that observed in human patients of AD. [5,34,46,47] On the macroscopic level, the skin of mice treated with DNBC exhibits an AD-like lesion; that is, it appears dry, red and rough: topical signs of a compromised barrier function. [46,48,49] The results of this study show that the AD-like lesions were successfully induced in the mice models as all the indexes of skin AD lesions (pH, TEWL and EASI) remarkably increased after 1 week of DNCB application compared with both the measurements performed before the application and the negative control group (group 6).…”
Section: Discussionmentioning
confidence: 99%